Identiteta migrantov: med integracijo in asimilacijo v luči paradoksov sodobnosti - Medica, Karmen (Monitor ISH, 2008)
The ubiquitous influence of migration processes in contemporary society calls attention to the fact that migration terminology has become politically dangerous and conceptually inapplicable. Despite the rapidly developing means of transport and the insignificance of time, there is an increasing control of movement. The West, which is popularly believed to be free of restriction on movement (the EU), is admittedly characterised by fast capital transfer and a regulated work tempo, but there is a growing awareness that movement in the modern world is rigorously regulated with a restrictive matrix of economic, political, gender, and cultural identities and affiliations.
Keywords: human migration; migracije; integracija; asimilacija; assimilation; prostor; čas; spol; varnost; security; identiteta